Scholarly Trends in Women Farmers’ Mental Health and Depression: Alignment With SDG Good Health and Wellbeing - Ndirangu, Ziporah; Zoltan, Egri (Acta Carolus Robertus, 2025)
Mental health and depression among women in agriculture remain critically underexplored despite their alignment with Sustainable Development Goal 3 on good health and well-being. This study adopts a feminist political ecology framework to examine how gendered power structures, environmental pressures, and unpaid labor intersect to shape the mental well-being of female farmers. A bibliometric analysis of 202 scholarly documents published between 2015 and 2024 was conducted using data from the Web of Science, analyzed through Biblioshiny and Microsoft Excel. Results show a rise in research output following the COVID-19 pandemic, with key themes including “women workers,” “occupational stress,” “empowerment,” and “gender roles.” Most studies are focused on regions such as Africa, India, and Bangladesh, where women play vital roles in agriculture. However, research partnerships remain limited within these regions, with most publications driven by institutions in high-income countries. The analysis highlights the gender bias in mental health research and calls for more inclusive, locally informed, and gender-sensitive approaches. This study urges policymakers to increase funding, strengthen regional collaboration, and integrate mental well-being into agricultural and rural development programs. By framing mental health as both a public health and gender equity issue, this work contributes to rethinking well-being in farming systems.
Keywords: Bibliometric Analysis; mental well-being; agriculture; health and safety; women